2020
DOI: 10.1016/j.jcf.2019.09.014
|View full text |Cite
|
Sign up to set email alerts
|

The implications of dysglycaemia on aerobic exercise and ventilatory function in cystic fibrosis

Abstract: Background: The development of cystic fibrosis (CF)-related diabetes (CFRD) in paediatric groups is associated with a reduced aerobic fitness. However, this has yet to be investigated in adults with more severe lung disease. Methods: Cardiopulmonary exercise and glycaemic control tests were retrospectively analysed in 46 adults with CF (age: 26.9 y [range: 16.3-66.5 y]; forced expiratory volume in 1s: 65.3% [range: 26.8-105.7%]; 26 males), diagnosed with CFRD (n = 19), impaired glucose tolerance (IGT; n = 8) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 33 publications
2
12
2
Order By: Relevance
“…Current UK guidelines on vitamin D supplementation for pwCF suggest 400–2000 IU day −1 for infants and 400–5.000 IU day −1 for children (> 1 year old) and adults with the aim of achieving a 25OHD concentration of > 50 nmol L −1 (20 ng ml −1 ) 39 . Despite vitamin D supplementation [1.400 (800–1.780) IU day −1 ] meeting current recommendations for pwCF in 86 (95%) of the study cohort, the prevalence of 25(OH)D deficiency and insufficiency (17% vs. 49%) was similar to that previously reported in pwCF elsewhere 10–41 and in children and adults diagnosed with cancer (33%–75%), who are either not supplemented or supplemented with lower doses of vitamin D (292–464 IU day −1 ), 11 and higher than the general UK population (19%–37%) 13 . Of note, supplementation in the general population is rare 13 .…”
Section: Discussionmentioning
confidence: 98%
“…Current UK guidelines on vitamin D supplementation for pwCF suggest 400–2000 IU day −1 for infants and 400–5.000 IU day −1 for children (> 1 year old) and adults with the aim of achieving a 25OHD concentration of > 50 nmol L −1 (20 ng ml −1 ) 39 . Despite vitamin D supplementation [1.400 (800–1.780) IU day −1 ] meeting current recommendations for pwCF in 86 (95%) of the study cohort, the prevalence of 25(OH)D deficiency and insufficiency (17% vs. 49%) was similar to that previously reported in pwCF elsewhere 10–41 and in children and adults diagnosed with cancer (33%–75%), who are either not supplemented or supplemented with lower doses of vitamin D (292–464 IU day −1 ), 11 and higher than the general UK population (19%–37%) 13 . Of note, supplementation in the general population is rare 13 .…”
Section: Discussionmentioning
confidence: 98%
“…However, the submaximal character of the 6mwt could be a possible explanation for these reported differences. Furthermore, Causer et al 17 indicated that CRF was reduced in adults with CFRD and IGT but that it is probably related to lung disease severity. The finding of Foster et al.…”
Section: Discussionmentioning
confidence: 99%
“…A eruginosa , which are all known co-morbidities and established predictors for survival in CF patients. 3 , 9 In the studies of Foster et al 14 and Causer et al 17 lower CRF levels were found for patients with impaired glucose tolerance (IGT) and CFRD compared to patients with normal glucose tolerance. However, variables as sex and age were included in their models, which are already known covariates for CRF in CF.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed incidence of CFRD rises with age, with increasing reported prevalence from 11 to 24% over 5 years ( Lanng et al, 1995 ). Given that the pancreas is one of the earliest affected organs in CF ( Gibson-Corley et al, 2016 ) and insufficiency is becoming a major determinant of morbidity and mortality ( Causer et al, 2020 ), the number of people being screened for CFRD has increased from 42% in 2004 to 81% in 2018 ( Ukcf Database, 2006 ; Cystic Fibrosis Trust, 2019 ). As prevention of CFRD is cited as a research priority within the CF community ( Rowbotham et al, 2018 ), there is a necessity for research that explore factors associated with CFRD.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies indicate that glucose intolerance is associated with poor clinical function ( Ziegler et al, 2011 ; Foster et al, 2018 ; Causer et al, 2020 ), although some report contradicting results in relation to CFRD and lung function. For example, forced expired volume in one second (FEV 1 ) and forced vital capacity (FVC) have been reported to be reduced in CFRD ( Koch et al, 2001 ; Causer et al, 2020 ), but a lack of difference (relative to those with normal glucose tolerance, NGT) is reported elsewhere ( Ziegler et al, 2011 ; Foster et al, 2018 ). Given the variability in the relationship between CFRD and FEV 1 , alternative factors must be investigated to create a detailed and holistic clinical profile for patients.…”
Section: Introductionmentioning
confidence: 99%